Assurdo e ridicolo. Ironia e deductio ad absurdum nella retorica forense - Sposito, Gianluca (Cultura giuridica e diritto vivente, 2018)
[Absurd and Ridicule. Irony and deductio ad absurdum in the Rhetoric] Irony is at the base of the Socratic speculative process, in which the interlocutor is in a way "ridiculed". Ridicule carries on functions similar to those of absurd in demonstration, i.e. reducing to ridicule is equivalent to reducing to absurdity. The use of argumentation by absurdity is also present in Roman rhetoric, particularly in Cicero, who makes use of ridiculum also as a rhetorical tool. Ridiculum is different both from the deductio ad absurdum - that is an argumentative tool - and from irony, that contributes to breake univocal sense frames and the atmosphere of seriousness that they involve. The argument for absurd (deductio ad absurdum) becames an argumentative scheme also for numerous jurists (particularly Celsus). This way of arguing does not absolutely consist in a simple expedient to confuse and ridicule the opponent. It is instead a rigorous logical process, subject to precise rules. In the legal sources ridicule is not used. Therefore it seems to be a purely oratory instrument, apparently not adequate to the reflections of the jurists and relegated to the oratory of the forum.